Survei Kondisi Fisik Atlet Joyoboyo Taekwondo Club (JTC) Kabupaten Kediri Usia Junior 15-17 Tahun - Firda Fitriana; Eko Hariyanto (Cahaya Ilmu Bangsa Institute, 2024)
The aim of this study was to find out the physical condition of Joyoboyo Taekwondo Club (JTC) Kediri Regency junior athletes aged 15-17 years. The method used is a survey with data collection techniques using tests and measurements. The population in this study were Joyoboyo Taekwondo Club (JTC) Kediri Regency athletes aged 15-17 years, totaling 18 athletes, with details of 12 male athletes and 6 female athletes, who were taken using total sampling techniques. In this study, the instruments used were test instruments in the form of strength tests (sit ups), endurance (balke), flexibility (sit and reach dynamometer), agility (T test), balance (standing stork test), speed (30 meter run) , explosive power in the leg muscles (standing broad jump). The data that has been obtained is then analyzed using quantitative descriptive analysis techniques. The results of this study show that the results of the abdominal muscle strength test (sit ups) for male and female athletes are predominantly in the